Adults with Treacher Collins Syndrome Share Comparable 3D Upper Airway Dimensions with Nonsyndromic Individuals - Renan Jhordan Mettelziefen dos Inocentes; Alexandre de Almeida Ribeiro; Maria Noel Marzano-Rodrigues; Marília Sayako Yatabe-Ioshida; Ivy Kiemle Trindade-Suedam (International Journal of Dentistry)
Purpose. Sleep apnea symptoms, such as snoring and daytime somnolence, are commonly observed in individuals with Treacher Collins Syndrome (TCS) and may be related to airway obstruction due to micro- and retro-gnathia. This study aims to three-dimensionally evaluate the upper airway using cone-beam computed tomography (CBCT) exams of adolescents (TCS-ADOL) and adults (TCS-ADUL) with TCS compared to a nonsyndromic group (CON). Materials and Methods. Twenty-six CBCT exams were divided into three groups: TCS-ADOL (n = 7) (13.14 ± 1.67 years): CBCT exams of TCS adolescents; TCS-ADUL (n = 10) (21.80 ± 4.39 years): CBCT exams of TCS adults; and CON (n = 9) (25.33 ± 8.57 years): CBCT exams of adult nonsyndromic individuals with Class II skeletal pattern. The variables analyzed were (1) total upper airway volume; (2) nasal cavity volume; (3) total pharyngeal volume; (4) nasopharyngeal volume; (5) oropharyngeal volume; (6) pharyngeal minimal cross-sectional area; (7) pharyngeal length; and (8) pharyngeal depth. Scans were analyzed by two examiners, and intra- and inter-rater agreement was calculated. A p-value of ≤0.05 was considered significant. Results. Although not statistically significant, the TCS-ADUL group showed decreased airway volume and minimal cross-sectional areas compared to the CON group. There were also significant differences between TCS-ADOL and TCS-ADUL, with significantly lower airway volumes in the TCS-ADOL group. Strong positive correlations were found between certain airway measurements in the TCS-ADOL group, which were not observed in adults. Conclusions. The upper airways of adults with TCS are dimensionally similar to those of nonsyndromic individuals, despite absolute value reductions found in the syndromic group. The reduced airway in the adolescent population suggests significant potential for growth, mainly in pharyngeal dimensions.